2020
DOI: 10.3847/1538-4357/ab5fe5
|View full text |Cite
|
Sign up to set email alerts
|

Optical Variability Modeling of Newly Identified Blazar Candidates behind Magellanic Clouds

Abstract: We present an optical variability study of 44 newly identified blazar candidates behind the Magellanic Clouds, including 27 flat spectrum radio quasars (FSRQs) and 17 BL Lacertae objects (BL Lacs). All objects in the sample possess high photometric accuracy and irregularly sampled optical light curves (LCs) in I filter from the long-term monitoring conducted by the Optical Gravitational Lensing Experiment. We investigated the variability properties to look for blazar-like characteristics and to analyze the lon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 117 publications
2
10
0
Order By: Relevance
“…Finally, given all the above considerations, the A − T plane, while potentially useful in classifying LCs (cf. Żywucka et al 2020;Tarnopolski et al 2020), does not hint at any clustering of long GRBs into more than one group (other than an overconcentration of flat PSDs at (1, 2 /3), likely owing to low signal-to-noise ratio), consistent with the findings of Jespersen et al (2020).…”
Section: The a − T Planesupporting
confidence: 70%
See 1 more Smart Citation
“…Finally, given all the above considerations, the A − T plane, while potentially useful in classifying LCs (cf. Żywucka et al 2020;Tarnopolski et al 2020), does not hint at any clustering of long GRBs into more than one group (other than an overconcentration of flat PSDs at (1, 2 /3), likely owing to low signal-to-noise ratio), consistent with the findings of Jespersen et al (2020).…”
Section: The a − T Planesupporting
confidence: 70%
“…The already proposed generation mechanisms (MRI (Masada et al 2007); precessing magnetic field (Ziaeepour & Gardner 2011)) can be complemented with some models employed for active galactic nuclei (AGNs), since both GRBs and AGNs often exhibit striking similarities (Wang et al 2014;Wu et al 2016;Deng et al 2016). In the simplest scenario, association of the break time scale with the viscous time scale of an accretion disk, coupled with the Keplerian motion on a circular orbit around the newly forming BH (Mohan & Mangalam 2014;Żywucka et al 2020) can explain the PSD breaks in GRBs as well. Since a relativistic two-body problem (in both Schwarzschild and Kerr metrics) allows for an inspiral (which is impossible in the Newtonian framework), occuring in a finite time (Levin & Perez-Giz 2008), a fragmented accretion disk could result in QPOs, lasting several cycles, and possibly chirping signals as well.…”
Section: Qposmentioning
confidence: 99%
“…Whether the stochastic process remains stationery on the timescales probed is crucial for understanding the physical processes operating on widely different spatial scales (e.g., Kushwaha et al 2016;Giebels & Degrange 2009). Studies of different blazars performed at different wavelengths have indeed revealed breaks in the slopes of PSDs, which could be attributed to the size of the emission zone or, alternatively, to cooling timescales of the particles (e.g., Abramowski et al 2010;Sobolewska et al 2014;Isobe et al 2015;Kastendieck et al 2011;Abdalla et al 2017;Ryan et al 2019;Żywucka et al 2020). The emerging picture of the broad-band blazar variability is that at higher energies (i.e., X−ray, and GeV and TeV γ−rays) is characterized by flicker/pink-noise processes (i.e., Abdalla et al 2017;Abdo et al 2010;Isobe et al 2015), whereas at lower energies (GHz band radio and optical frequencies) damped/red-noise type processes dominate (i.e., Ciprini et al 2007;Kastendieck et al 2011;Park & Trippe 2014;Max-Moerbeck et al 2014b;Nilsson et al 2018).…”
mentioning
confidence: 99%
“…The FSRQs are characterised by lower values of A than BL Lacs and these two classes of blazars are clearly separated on the A − T plane (Figure 3). This was earlier discovered by [13]…”
Section: Resultsmentioning
confidence: 70%